ANALISIS KEMAMPUAN KOGNITIF SISWA PADA TEMA LINGKUNGAN SAHABAT KITA DI KELAS V SD INPRES SRITABAANG - Rai Widiani, Dewa Ayu Putu; Putrayasa, I Wayan Budiagus; Hariani, Ni Made Mega (JATMIKA : Journal Education and Learning of Elementary School, 2024)
the inhibiting factors of students' cognitive abilities on the theme of our friendly environment in class V SD Inpres Sritabaang. Determination of informants with purposive sampling. The methods used: observation, tests, interviews, documentation and validation sheets. Based on the results of the pre-test scores of 29 students who got sufficient category scores with an average score of 58.37, namely 8 students, and students who got less category scores with an average score of 48.9 were 21 students, the highest score in the pre-test namely 63 with an average score of 50.93. Meanwhile, the results of the post test scores of 29 students who got sufficient category scores with an average score of 62.70, namely 15 students, students who got less category scores with an average score of 49.49 were 13 students, and 1 student who got a score in the good category, the highest post-test score was 73 with an average score of 57.34. In the results of interviews conducted by researchers with fifth grade students at SD Inpres Sritabaang, it was found that the inhibiting factors for students' cognitive abilities came from: internal factors and external factors, in which internal factors were influenced by physical factors and psychological factors, while external factors were influenced by family factors, friend and environmental factors.